2006
DOI: 10.1093/nar/gkl036
|View full text |Cite
|
Sign up to set email alerts
|

3dSS: 3D structural superposition

Abstract: 3dSS is a web-based interactive computing server, primarily designed to aid researchers, to superpose two or several 3D protein structures. In addition, the server can be effectively used to find the invariant and common water molecules present in the superposed homologous protein structures. The molecular visualization tool RASMOL is interfaced with the server to visualize the superposed 3D structures with the water molecules (invariant or common) in the client machine. Furthermore, an option is provided to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 25 publications
0
78
0
Order By: Relevance
“…Superposition and location of invariant water molecules were made using the program 3dss (21). Interfacial water molecules were located with the program Water Analysis Package (22).…”
Section: Methodsmentioning
confidence: 99%
“…Superposition and location of invariant water molecules were made using the program 3dss (21). Interfacial water molecules were located with the program Water Analysis Package (22).…”
Section: Methodsmentioning
confidence: 99%
“…Docking studies revealed that the "hydrophobic tail" at the amp-2 N-terminus has a key role in membrane interaction (Figure 6b) 49 , forming a hydrogen interaction between nitrogen (ND2) and oxygen, respectively, with a distance of 2.8 Å. The "hydrophobic tail" added into amp-2 also showed an interesting property since it probably involved a hydrogen bond formation between nitrogen (N7) of modification and oxygen head group (O14) in DPPE 18 with a distance of 2.8 Å (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…In the amp-2 interaction toward a Gram-positive membrane (Figure 7b) it was possible to identify the insertion into membrane core involving the "hydrophobic tail" (C 6 H 12 N). This insertion is probably firstly guided through hydrogen bond formation between nitrogen (N7) and oxygen head group of phospholipids DPPE 18 with a distance around 3.3 Å. Probably hydrophobic interactions inside the core might be formed with the insertion of the "hydrophobic tail", since the distance observed was less than 3.5 Å ( Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one may find it interesting to note that the strands 2 and 3 are intact in all the time averaged structures. Further, superposition of the crystal and simulated structures performed using 3dss [34] revealed that the 2 and 3 -strands are preserved in their respective orientations (data not shown). The time averaged native and mutant structures show a decrease in content of secondary structural elements.…”
Section: Assessment Of Secondary Structuresmentioning
confidence: 98%